COVID-19 vaccination at a hospital in Paris: Spatial analyses and inverse equity hypothesis - Valéry Ridde; Gaëlle André; Olivier Bouchaud; Emmanuel Bonnet (Elsevier, 2024)
Background: Vaccination against SARS-CoV-2 has been deployed in France since January 2021. Without specific action for different population subgroups, the inverse equity hypothesis postulates that people in the most deprived neighbourhoods will be the last to benefit. The article aims to study whether the inverse care law has been verified in the context of vaccination against SARS-CoV-2 from a vaccination centre of a hospital in the Paris region. Methods: We performed a spatial analysis using primary data from the vaccination centre of the Avicenne Hospital in Bobigny from January 8th to September 30th, 2021. Primary data variables include the vaccinated person's date, age, and postal address. Secondary data calculates access times between residential neighbourhoods and the vaccination centre and social deprivation index. We performed flow analysis, k-means aggregation, and mapping. Results: 32,712 people were vaccinated at the study centre. Vaccination flow to the hospital shows that people living in the most disadvantaged areas were the last to be vaccinated. The number of people immunized according to the level of social deprivation then scales out with slightly more access to the vaccination centre for the most advantaged. The furthest have travelled more than 100 km, and more than 1h45 of transport time to get to this vaccination centre. Conclusion: The study confirms the inverse equity hypothesis and shows that vaccination preparedness strategies must consider equity issues. Public health interventions should be implemented according to proportionate universalism and use community health, health mediation, and outreach activities for more equity.